Primary schooling in India - Sinha, Amarjeet (New Delhi, 1998)
Primary Schooling in India" is an attempt to understand the state of Primary Education in India. Based on extensive field trips to a large number of states and an analysis of secondary sources, the author has attempted to capture the challenge of education for all.
Keywords: Education